2017
DOI: 10.1002/cbf.3244
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of neurotrophic factors and inhibition of proinflammatory cytokines by exogenous application of triiodothyronine in the rat model of ischemic stroke

Abstract: There is a positive relation between decreases of triiodothyronine (T3) amounts and severity of stroke. The aim of this study was to evaluate the effect of exogenous T3 application on levels of neurogenesis markers in the subventricular zone. Cerebral ischemia was induced by middle cerebral artery occlusion in male Wistar rats. There were 4 experimental groups: sham, ischemic, vehicle, and treatment. Rats were injected with T3 (25 μg/kg, IV injection) at 24 hours after ischemia. Animals were sacrificed at day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 18 publications
(46 reference statements)
0
19
0
Order By: Relevance
“…Two studies reported evident reductions of tissue infarction and edema in a transient middle cerebral artery occlusion (t-MCAO) model of male mice injected with T3, and attributed this anti-edema effect to suppression of the expression of aquaporin-4 (AQP4) water channels by T3 36 , 37 . Studies also found that T3 and T4 could inhibit apoptosis, resist excitability-related amino acid toxicity, suppress inflammatory reactions and increase ATP production by stimulation of astrocyte fatty acid oxidation in animal models of brain ischemia 34 , 35 , 38 , 39 . However, other experiments reported contradictory discoveries.…”
Section: Discussionmentioning
confidence: 97%
“…Two studies reported evident reductions of tissue infarction and edema in a transient middle cerebral artery occlusion (t-MCAO) model of male mice injected with T3, and attributed this anti-edema effect to suppression of the expression of aquaporin-4 (AQP4) water channels by T3 36 , 37 . Studies also found that T3 and T4 could inhibit apoptosis, resist excitability-related amino acid toxicity, suppress inflammatory reactions and increase ATP production by stimulation of astrocyte fatty acid oxidation in animal models of brain ischemia 34 , 35 , 38 , 39 . However, other experiments reported contradictory discoveries.…”
Section: Discussionmentioning
confidence: 97%
“…Thyroid hormones (THs), including triiodothyronine (T3) and thyroxine (T4), are essential for brain development, morphogenesis and maturation processes [11]. Studies in animal stroke model have shown that T3 has therapeutic effects on cerebral ischemic stroke by increasing the neurotrophic factors and in vitro reduction of inflammation and restoration of neurotrophin expression, which lead to better neurological function [12, 13]. Despite the mechanisms depicted by the above studies, the detailed signaling pathways by which T3 affects functional outcome of stroke patients remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…- Sabbaghziarani et al 2017: similar to previous study from Mokhtari et al (2017), here cerebral ischemia was induced by MCAo in male Wistar rats; a group of rats was also injected with T3 (25 μg/kg, IV injection) at 24 hours after ischemia. BDNF gene and protein levels (along with nestin and Sox2) were increased upon T3 treatment vs ischemic group.…”
Section: Empirical Evidencementioning
confidence: 71%